Responses of human soleus motor units to low-threshold stimulation of the tibial nerve - Binboǧa E. (2017)
The peristimulus frequencygram (PSF) has recently been shown to illustrate postsynaptic potentials of motoneurones much more reliably than the peristimulus time histogram (PSTH). The aim of this investigation was to examine the profile of the postsynaptic potential (PSP) in soleus motoneurones in response to an H-reflex with and without accompanying M waves of different magnitude by using PSTH and PSF profiles of single motor units. Nine men and five women healthy subjects participated in this study. Electrical stimuli were delivered to the tibial nerve in the popliteal fossa. The reflex response of the soleus muscle was recorded using both surface electromyogram and single motor unit potentials. The PSTH analysis demonstrated that there were four different synaptic events following low-intensity stimulation of the tibial nerve: primary enhancement in firing probability (H-reflex or E1), primary reduction in firing probability (primary silent period or SP1), secondary reduction in firing probability (secondary silent period or SP2), and secondary enhancement in firing probability (E2). On the other hand, the PSF analysis indicated only two reflex responses, long-lasting enhancement in discharge rate including the H-reflex (LLE) and long-lasting decrease in discharge rate (LLD). The results of the two analyses methods are compared and contrasted. While the PSTH demonstrated that there was a silent period (SP1) immediately following the H-reflex, the PSF indicated an increase in discharge rate during the same period. The PSF also indicated that, during SP2 and E2, the discharge rate actually decreased (LLD). It was therefore suggested that LLD involved activation of several inhibitory pathways including the autogenic inhibition of units via the Golgi tendon organs. It was concluded that the PSF could indicate the details of the postsynaptic potentials and is very useful for bringing out previously unknown effects of electrical stimulation of muscle nerves. © 2011 Springer-Verlag.